2019
DOI: 10.1007/978-3-030-14094-6_2
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Routing in Hybrid Communication Networks

Abstract: Routing is a challenging problem for wireless ad hoc networks, especially when the nodes are mobile and spread so widely that in most cases multiple hops are needed to route a message from one node to another. In fact, it is known that any online routing protocol has a poor performance in the worst case, in a sense that there is a distribution of nodes resulting in bad routing paths for that protocol, even if the nodes know their geographic positions and the geographic position of the destination of a message … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 21 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…Our objective is to design a competitive routing algorithm for ad hoc networks, where the source s of a message knows the ID of the destination t, or in other words, (s, t) ∈ E. We call a routing strategy c-competitive, if the length of a path obtained by the strategy has length at most c times the length of an optimal path for a constant c. The authors in [13] have shown that any online routing algorithm that only has local knowledge about the network cannot be c-competitive. Based on these results, the authors in [10] proposed a strategy that makes use of a Hybrid Communication Network to obtain information about location and shapes of holes. They have proven that in case the convex hulls of radio holes do not intersect, their approach finds c-competitive paths in the ad hoc network.…”
Section: Objectivementioning
confidence: 99%
See 4 more Smart Citations
“…Our objective is to design a competitive routing algorithm for ad hoc networks, where the source s of a message knows the ID of the destination t, or in other words, (s, t) ∈ E. We call a routing strategy c-competitive, if the length of a path obtained by the strategy has length at most c times the length of an optimal path for a constant c. The authors in [13] have shown that any online routing algorithm that only has local knowledge about the network cannot be c-competitive. Based on these results, the authors in [10] proposed a strategy that makes use of a Hybrid Communication Network to obtain information about location and shapes of holes. They have proven that in case the convex hulls of radio holes do not intersect, their approach finds c-competitive paths in the ad hoc network.…”
Section: Objectivementioning
confidence: 99%
“…To do so, we replace the computation of convex hulls of holes by the computation of bounding boxes. In addition to [10], we also propose a strategy for intersecting bounding boxes.…”
Section: Objectivementioning
confidence: 99%
See 3 more Smart Citations